2001
DOI: 10.1016/s0377-1237(01)80046-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Midazolam and Thiopentone as Induction Agents in General Anaesthesia

Abstract: A single blind parallel group study was performed in 137 patients undergoing elective surgery under general anaesthesia to compare the efficacy and tolerability of midazolam 0.15 to 0.25 mglkg or thiopentone 6 mglkg. Induction time was 45.0±17.1 sees in midazolam group in comparison to 32.0±9.5 sees in thiopentone group and the frequency of apnoea was 11.5% and 17.1% respectively. There was no difference in the duration of apnoea in the two groups. No venous intolerance was experienced during the study. It app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Earlier study by Coolong KJ et al had similar result where the surgical procedure continued longer than 2 hours. 10 This is in contrast to studies by Shah PJ et al and Henriksson BA et al which showed that propofol has significantly shorter recovery time than thiopentone. 4,12 This could be explained by the very short procedures which they studied.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Earlier study by Coolong KJ et al had similar result where the surgical procedure continued longer than 2 hours. 10 This is in contrast to studies by Shah PJ et al and Henriksson BA et al which showed that propofol has significantly shorter recovery time than thiopentone. 4,12 This could be explained by the very short procedures which they studied.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, they have got significant pharmacokinetic and pharmacodynamic variability. 1,9,10 Thiopentone is the most commonly used intravenous induction agent in elderly people. There was no significant difference in the time to loss of eye lash reflex in the propofol and thiopentone groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation